Characteristics and petroleum geological significance of high-quality source rock in Gufeng Member of Middle Permian Maokou Formation in northern Sichuan Basin, China. Issue 1 (November 2020) - Fu, X D; Chen, Y N; Wang, X F; Lv, X J; Li, W Z; Yao, Q Y
Abstract: Based on the comprehensive analysis of drilling and outcrop profile data, the stratigraphic boundary between Middle Permian and Upper Permian in northern Sichuan Basin is redefined systematically. It is confirmed that the source rock of carbonaceous and siliceous mudstone is widely developed in the Gufeng Member of Middle Permian Maokou Formation in the northern part of the basin, and its thickness is mainly between 5-40 m. The source rock in the Gufeng Member has large variation scope of TOC, mainly in the range of 0.5%-30%, and the average value of most profiles more than 2.0%. It is a set of high-quality source rock as a whole. Its major organic matter is type II. At present, its thermal maturity changes greatly, and it is in the mature-over mature stage. The deep-water sedimentary environment, strong reduction conditions and high paleo-productivity jointly controlled the development and distribution of high-quality source rock in the Gufeng Member under the background of extensional structure at the end of the Middle Permian. High-quality source rock in the Gufeng Member is of great significance to the exploration of marine conventional natural gas and shale gas in northern Sichuan Basin.